Novel AGL variants in a patient with glycogen storage disease type IIIb and pulmonary hypertension caused by pulmonary veno-occlusive disease: A case report - Shindo, Akito; Ueda, Kazutaka; Minatsuki, Shun; Nakayama, Yukiteru; Hatsuse, Satoshi; Fujita, Kanna; Nomura, Seitaro; Hatano, Masaru; Takeda, Norifumi; Akazawa, Hiroshi; Komuro, Issei (Frontiers in Genetics, 2023)
Glycogen storage disease type III (GSD-III) is an autosomal recessive metabolic disorder caused by mutations in the AGL gene, and may develop various types of pulmonary hypertension (PH). Here, we report a case of 24-year-old man with GSD-IIIb with two novel null variants in AGL (c.2308 + 2T>C and c.3045_3048dupTACC). He developed multi-drug-resistant pulmonary veno-occlusive disease (PVOD) and was registered as a candidate for lung transplantation. No pathogenic variants were detected in previously known causative genes for pulmonary hypertension and the underlying mechanism of coincidence of two rare diseases was unknown. We discuss the association of the loss of glycogen-debranching enzyme with incident PVOD.